Partisipasi Masyarakat Dalam Perencanaan Pembangunan Kecamatan Cempaga Hulu Kabupaten Kotawaringin Timur: Community participation in the development planning of the District Cempaga Hulu District kotawaringin East - Ratmoko, Ambar; Medahrina, Medahrina (Pencerah Publik, 2016)
This research aims as an effort to give an overview of community participation in development planning in the district of Cempaga Hulu East Kotawarwants District. The type of research used is qualitative research methods. The source of primary data is district officers, head of DEA and community of Upper Bland. While its secondary data is community participation in development planning. Data analysis using qualitative data analysis procedures are data reduction and withdrawal of conclusions. Based on the results of the research can be explained that the community participation in development planning is low because (1) the community is less clear information about the opportunities provided to participate in the utilization of the results Development. (2) The lack of proximity or solicitation from the district government to the local community is either from giving information to the community. (3) The ability of governments involving communities is also low.